PERSPEKTIF ALKITAB TERHADAP KATEGORI PENGIKUT DALAM TEORI KEPENGIKUTAN ROBERT KELLEY - Setiadarma, Ferijanto (SEKOLAH TINGGI TEOLOGI DAN ENTREPRENEURSHIP PRINGGADING (STEP) SEMARANG, 2025)
The abundance of studies on Leadership theory and practice needs to be balanced with an explanation of Followership theory and practice, considering that followership is a critical element in Leadership studies that is rarely observed. One quite phenomenal aspect of Followership Theory is the categorization of followers initiated by Robert Kelley. Kelley stated that so far there are five categories of followers. The researcher wanted to see what the Bible's perspective is on Kelley's five categories of followers. This is very important considering that in the Bible there are quite a lot of leaders used by God but the behavior of the followers of those leaders is rarely described. This study uses a qualitative method with a literature study approach and exegesis of several biblical passages related to Followership and its implications for the practice of Christian Leadership today.